STUDIES ON AMLAPITTA W.S.R. TO RAKTADUSTI & RAKTAJA ROGA - Porel, *Kaushik; Ray, Sukalyan (International Journal of Ayurveda and Pharma Research, 2017)
Amlapitta is a disease where there is vitiation of Pitta dosha in general and Amla Guna of Pitta in specific. In the primary compendiums, the disease Amlapitta has not been mentioned separately. This disease was first described as a separate entity in Madhav Nidan, and thereafter in Kashyap Samhita and Bhavprakash. Although Acharya Charak has not mentioned this disease separately, the causative factor and clinical feature of Raktadusti and Raktaja Roga mentioned by him are very similar to that of Amlapitta. Pitta and Rakta are two identical elements of body. Due to the similarities in between Pittaand Rakta, the former afflicts more the later. In this study, the literary information regarding the similarities between Raktadusti, Raktaja Roga and Amlapitta have been verified through clinical study. A comparative discussion has been carried out between the causative factors and clinical features of Raktadusti, Raktaja Roga and Amlapitta. The study has been also carried out to evaluate the efficacy of Amlaki (Emblica officinalis Gaertn.), which is a well-known drug clinically effective on Raktadusti and Raktaja Roga due to its Tikta, Madhura and Kashaya rasa, Madhur Vipaka and Sheeta Virya. This subsequently helps to combat Amlapitta. Fresh juice of fruit pulp of Amlaki (Emblica officinalis Gaertn.) was administered in the selected 30 patients at a dose of 50 ml per day, at early morning and in empty stomach for a period of 21 days. After 21 days, effect of the stipulated drug was evaluated in 27 patients with 3 dropouts. The subjective and objective parameters have been evaluated before and after treatment. All the findings have been statistically analyzed using paired t test. The obtained results have been interpreted as – p <0.05 is significant & p <0.001 is highly significant. The results showed p value <0.001 in most of the parameters (subjective and objective), which indicates that, the drug taken for the present study i.e. Amalaki is highly efficacious against Raktadusti & Raktaja Roga and subsequently very helpful to combat Amlapitta.